Enterprise Architecture Using TOGAF ADM to Support Smart Campus at STAI Raudhatul Akmal - Rizky Rinaldi; Khairul, Khairul; Rian Farta Wijaya; Nasution, Darmeli; Siahaan, Andysah Putera Utama (Jurnal Info Sains : Informatika dan Sains, 2024)
The development of an academic information system to support the Smart Campus concept at STAI Raudhatul Akmal requires an effective enterprise architecture approach. This study adopts the TOGAF ADM method to design an enterprise architecture that can accommodate evolving academic and technological needs. The focus is on applying TOGAF ADM to analyze academic business processes and develop an integrated system implementation plan. Primary data sources include analyses of academic business processes at STAI Raudhatul Akmal, covering student admissions, teaching and learning, research, community service, graduation, and alumni services. Using TOGAF ADM’s eight phases—including vision architecture, business architecture, information system architecture, technology architecture, and change management—this study aims to develop a blueprint aligned with institutional needs. The analysis results indicate that the architectural blueprint includes a web-based information system, e-learning system, online grading system, and library system. The technology design covers network infrastructure and servers. The implementation governance and change management phases highlight the importance of systematic change management to ensure a smooth transition. This study recommends assessing institutional readiness and implementing all aspects of TOGAF ADM for a comprehensive design to effectively support the Smart Campus implementation at STAI Raudhatul Akmal.